2011
DOI: 10.1124/mol.111.072967
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Preventive Rexinoid Modulates Neutral Lipid Contents of Mammary Epithelial Cells through a Peroxisome Proliferator-Activated Receptor γ-Dependent Mechanism

Abstract: Synthetic rexinoids effectively suppress both estrogen receptor-positive and estrogen receptor-negative mammary tumors in animal models, which makes them prime candidates for a novel class of cancer-preventive agents. When used in combination with chemotherapy for non-small-cell lung cancer, the rexinoid bexarotene was most effective for patients who developed hypertriglyceridemia as a side effect. Although serum triglycerides originate from the liver, the effect of bexarotene on lipogenesis in breast epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Photoacoustic imaging of the mouse mammary tumor virus-polyoma middle T (MMTVPyMT)-driven breast cancer model demonstrated that transformation of normal breast tissue to invasive carcinoma resulted in a progressive decrease of cytoplasmic LD abundance (29). In line with this finding, pharmacological activation of peroxisome proliferatoractivated receptor-γ caused accumulation of LDs in breast cancer cells and decreased their proliferation (30). Furthermore, Src (31) and Myc (32) oncogenes were recently reported to contribute to lipid metabolism dysregulation in TNBC.…”
Section: Significancementioning
confidence: 79%
“…Photoacoustic imaging of the mouse mammary tumor virus-polyoma middle T (MMTVPyMT)-driven breast cancer model demonstrated that transformation of normal breast tissue to invasive carcinoma resulted in a progressive decrease of cytoplasmic LD abundance (29). In line with this finding, pharmacological activation of peroxisome proliferatoractivated receptor-γ caused accumulation of LDs in breast cancer cells and decreased their proliferation (30). Furthermore, Src (31) and Myc (32) oncogenes were recently reported to contribute to lipid metabolism dysregulation in TNBC.…”
Section: Significancementioning
confidence: 79%
“…A growth arrest in cells with active lipid synthesis may trigger the cells to redirect the flux of FA from membrane lipid synthesis to the synthesis of storage lipids, to avoid an accumulation of excess membranes. This hypothesis is supported by the fact that PPARγ agonists act synergistically with rexinoids [152]. However, the detailed mechanisms of rexinoid action remain to be elucidated.…”
Section: Neutral Lipid Homeostasis: How To Deal With Excess Fatty Acidsmentioning
confidence: 96%
“…Synthetic RXR ligands, also termed rexinoids, are under investigation as potent agents in therapy for several cancers. Bexarotene induces the accumulation of triacylglycerol in cytosolic lipid droplets and leads to an arrest of cell proliferation, with PPARγ agonists acting synergistically to inhibit tumor growth [152]. In cells treated with bexarotene mRNA expression of acyl-CoA synthetase 1, stearoyl-CoA dehydrogenase and diacylglycerol acyltransferase, key enzymes of FA and TAG metabolism, are induced; another important factor in lipid homeostasis, adipophilin, is elevated at the protein level upon treatment [152].…”
Section: Neutral Lipid Homeostasis: How To Deal With Excess Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach is to examine potential enhancing interactions among the multitude of partnering nuclear hormone receptors. This way anti-proliferative and anti-tumor cooperation was demonstrated between RXRs and PPARs in premalignant mammary epithelial cells, as well as in vivo [156, 157]. …”
Section: The Use Of Retinoids For Cancer Preventionmentioning
confidence: 99%